SIT TO STAND TEST OSTEOARTHRITIS PATIENTS - Aisyah; Marselli Widya L; Anisgupta Larasaty F (UNUSA Press, 2020)
Osteoarthritis is a disease found in the elderly or often called a degenerative disease. The prevalence of total osteoarthritis in Indonesia was 34.3 million in 2002 and reached 36.5 million in 2007. An estimated 40% of the population above 70 years old suffer from osteoarthritis, and 80% of osteoarthritis patients have limited mobility in various degrees from mild to severe resulting in reducing the quality of life because of the high prevalence. The development of a simple approach to quantitatively estimating functional motor performance in various ages is very important for early detection of locomotive syndrome (LS), one of which is the sit to stand test (STST). In Indonesia, there are no studies that discuss STST, so the cut off point or even the average can be different. This can be influenced by differences in culture, demographics, activities, or treatment regimens. Based on the problem above, the researcher tries to find out the average and standard deviation of STST scores in Osteoathritis patients at Ahmad Yani Hospital, Surabaya by accidental sampling method on secondary data, namely Medical Records in 2019 at the Rehab ilitation outpatient clinic of Ahmad Yani Hospital in August-September 2019. The data recorded is in the form of quantitative data in units of seconds. Furthermore, the data is processed using SPSS 17 and displays the average value and standard deviation.